2016
DOI: 10.1002/for.2440
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐model Forecasts of the West Texas Intermediate Crude Oil Spot Price

Abstract: We measure the performance of multi‐model inference (MMI) forecasts compared to predictions made from a single model for crude oil prices. We forecast the West Texas Intermediate (WTI) crude oil spot prices using total OECD petroleum inventory levels, surplus production capacity, the Chicago Board Options Exchange Volatility Index and an implementation of a subset autoregression with exogenous variables (SARX). Coefficient and standard error estimates obtained from SARX determined by conditioning on a single ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Furthermore, using a quadratic error measure leads to a penalization of comparatively large forecast errors. The RMSE given in Formula below is one very commonly applied error measure (see, e.g., Andres & Spiwoks, ; Espinoza, Fornari, & Lombardi, ; Hyndman & Koehler, ; Kisinbay, ; Leitch & Tanner, ; and more recently Herwartz & Schlüter, ; Ryan & Whiting, ; as well as Wegener, Spreckelsen, Basse, & Mettenheim, ). lefttrueitalicRMSEBrent,hitalicj=1Nfalse∑i=1N()pitalicBrent,i,hp̂italicBrent,i,hj2anditalicRMSEWTI,hitalick=1Nfalse∑i=1N()pitalicWTI,i,hp̂italicWTI,i,hk2. …”
Section: Methodologies Of Forecast Evaluationmentioning
confidence: 99%
“…Furthermore, using a quadratic error measure leads to a penalization of comparatively large forecast errors. The RMSE given in Formula below is one very commonly applied error measure (see, e.g., Andres & Spiwoks, ; Espinoza, Fornari, & Lombardi, ; Hyndman & Koehler, ; Kisinbay, ; Leitch & Tanner, ; and more recently Herwartz & Schlüter, ; Ryan & Whiting, ; as well as Wegener, Spreckelsen, Basse, & Mettenheim, ). lefttrueitalicRMSEBrent,hitalicj=1Nfalse∑i=1N()pitalicBrent,i,hp̂italicBrent,i,hj2anditalicRMSEWTI,hitalick=1Nfalse∑i=1N()pitalicWTI,i,hp̂italicWTI,i,hk2. …”
Section: Methodologies Of Forecast Evaluationmentioning
confidence: 99%
“…Also, they can be stored to be sold at higher prices in the future. This is called speculative inventory [119][120][121][122].…”
Section: Inventoriesmentioning
confidence: 99%
“…Ye et al presented a model for forecasting short-term oil prices using only lagged OECD petroleum inventory levels as explanatory variables, providing a wellfitted forecast both in-sample and out-of-sample. Ryan and Whiting (2016) found that the OECD inventory level lagged by two months had a significant relationship with oil prices. Inventory levels are generally accepted as an important fundamental factor when explaining oil price dynamics (Hamilton 2008;He et al 2010;Kilian and Murphy 2014;Merino and Ortiz 2005).…”
Section: Supply Factorsmentioning
confidence: 99%
“…For instance, Sarwar (2012) found a strong negative correlation between changes in VIX and US stock market returns. Ryan and Whiting (2016) found that the VIX, lagged with one month, was the most important indicator in terms of forecasting oil prices. A large amount of literature has examined the relationship between oil prices and the stock market (Bernanke 2016;Hammoudeh et al 2004;Kang et al 2015;Sadorsky 1999), generally explaining a significant positive correlation between the two.…”
Section: Financial Factorsmentioning
confidence: 99%